Use of Grade 1 Liquid Smoke from Apus Bamboo (Gigantochia apus) Raw Material as A Preservative for Fresh Shrimp by Soaking Method at Different Concentrations - Ita Merni; Akbar Pratama; Erina Hertianty; Taman Alex; Zahrotul Isti'anah Marroh; Teguh Rizali Zahroni (Jurnal Loupe, 2024)
This research is motivated by the lack of optimal use of bamboo, where bamboo is a natural material that is relatively cheap, easy to obtain and is one of the plants whose use in society is less optimized. In its role as a plant, bamboo can also be used as a material for making liquid smoke for various food needs which can be used for preservation. Shrimp is also a food that people really like, but shrimp cannot last long so natural additives are needed so that shrimp can last longer. Therefore, this research aims to determine the effect of providing liquid smoke from bamboo on shrimp quality, including changes in the smell and texture of shrimp. Observations were carried out at the Non-Wood Forest Products Laboratory, Forest Products Processing Study Program, Samarinda State Agricultural Polytechnic. The research method was carried out by observing shrimp without preservation (control), preserving shrimp with different concentrations, namely 5%, 7% and 9%. Observations of changes in the smell and texture of preserved shrimp were carried out for 6 days. The research results showed that preserving shrimp using liquid smoke from grade 1 bamboo material at a concentration of 7% was more effective than the control, liquid smoke concentrations of 5% and 9%.